The public spaces of the new city Ali Mendjeli: between attendance and use - Yahi, Amel; Dekoumi, Djamel (Journal of Human Sciences, 2020)
The ambition of this article is to take into account the "commercialisation" of public spaces in this new so-called modern society. Based on the example of the new city Ali Mendjeli, this work attempts to identify public spaces with the new city in the current context, with the aim of moving away from the usual and theoretical methods for an in situ analysis of what is really happening in the field. Observing the in situ behaviours of users of public spaces means studying their daily lives in their movements and behaviours, in order to understand the impact of the environment (the city, development) on people in their daily lives. The idea here is that the material support of public spaces is inseparable from the activities and practices that form them. Draw conclusions about the influence of the city’s morphology on man and their activities.